Severe Homozygous Protein C Deficiency: Identification of a Splice Site Missense Mutation (184, Q → H) in Exon 7 of the Protein C Gene - Soria, J M; Brito, D; Barceló, J; Fontcuberta, J; Botero, L; Maldonado, J; Estivill, X; Sala, N (Thrombosis and Haemostasis, 1994)
Single strand conformation polymorphism (SSCP) analysis of exon 7 of the protein C gene has identified a novel splice site missense mutation (184, Q → H), in a newborn child with purpura fulminans and undetectable protein C levels. The mutation, seen in the homozygous state in the child and in the heterozygous state in her mother, was characterized and found to be a G to C nucleotide substitution at the -1 position of the donor splice site of intron 7 of the protein C gene, which changes histidine 184 for glutamine (184, Q → H). According to analysis of the normal and mutated sequences, this mutation should also abolish the function of the donor splice site of intron 7 of the protein C gene. Since such a mutation is compatible with the absence of gene product in plasma and since DNA sequencing of all protein C gene exons in this patient did not reveal any other mutation, we postulate that mutation 184, Q → H results in the absence of protein C gene product in plasma, which could be the cause of the severe phenotype observed in this patient.